Распределители ремней конской упряжи VII—VI вв. до н. э. в Закавказье и Передней Азии - Махортых, С.В. (Археологія і давня історія України, 2018)
Статья посвящена пространственно-хронологическому анализу металлических и роговых уздечных пронизей для ремней конского оголовья бытовавших в Закавказье и Передней Азии в VII—VI вв. до н. э. The article is devoted to the analysis of different types of metal and bone harness fittings of VII—VI centuries BC which were found in the South Caucasus and the Near East. Among those fittings, which are constituted about 50 artifacts, two major groups could be distinguished: plain fittings of various geometric shapes and fittings with zoomorphic decorations. The latter group dominates and constitutes about 80 % of the total number of findings. The major regions of distribution of these horse harness attachments are Armenia and Turkey. The cylindrical harness fittings of the first type from the group 1 were the most widespread among the geometrical samples (8 items), while among the zoomorphic ones — claw-shaped, or beak-shaped objects of type 1 from the group 2 (19 items). It should be noted that the majority of the analyzed finds were found not in burial monuments, as in the Northern Caucasus and in the Ukrainian forest-steppe, but at settlements. The emergence of the tradition of manufacturing, as well as the widespread using of various types of harness fittings, and primarily the zoomorphic ones, to the South of the main Caucasian ridge, was the result of the staying and activity on this territory of the Scythians of the South of Eastern Europe. The main period of existence of strap-dividers in Transcaucasia and the Near East was the second half of the VII — the first half of the VI centuries BC.